Investigation of Variables that Determine Levels of Self-Esteem in Central American Schoolchildren: A Binary Logistic Regression Model - Álvarez Bogantes, Carlos; Herrera-Monge, María Fernanda; Herrera-González, Emmanuel; Araya-Vargas, Gerardo A. (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2021)
The purpose of this research was to examine the relationships between the levels of self-esteem of Central American schoolchildren and their physical activity habits, ages and countries of origin. This was a correlational study of random cluster probabilistic samples, which evaluated 5,291 students enrolled in fourth, fifth and sixth grades, 52.3% of whom were girls and 47.7% boys, from 74 schools in Guatemala, Honduras, El Salvador, Costa Rica, Nicaragua and Panama, with an average age of 10.90 ± 1.13 years. Lawrence’s Self-Esteem Questionnaire (LAWSEQ) was used to measure levels of self-esteem, and the physical activity questionnaire for boys and girls (PAQ-C) was applied in all the countries. A binary logistic regression analysis was carried out to estimate the statistical probability that the independent variables (age, level of activity and country of origin) could predict the level of self-esteem. The results of this investigation showed that 47% of the children studied perceive themselves to have a low level of physical activity, and that children from 9 to 10 years had lower percentages of self-esteem with 51.6% and 47.7%, respectively. In terms of country of origin, children from Costa Rica and Guatemala have a better level of self-esteem than those living in El Salvador, Nicaragua, Honduras and Panama. In addition, it was determined that age, level of physical activity and country of origin predicted 58% of the level of self-esteem of Central American children. This shows the importance of promoting physical activity in childhood to contribute to the development of self-esteem.